Management in China During the Age of ReformManagement in China During the Age of Reform, by ChildJohn. Cambridge, England: Cambridge University Press, 1994. - Shenkar, Oded (Academy of Management Review, 1996)
The article reviews the book ?Management in China During the Age of Reform,? by John Child.